PENGARUH METODE PEMBELAJARAN EKSPLORASI DAN MINAT SISWA TERHADAP HASIL BELAJAR PASSING BAWAH BOLA VOLI DALAM PEMBELAJARAN PENJASORKES (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
AbstrakPenelitian ini bertujuan mengetahui perbedaan pengaruh antara metode pembelajaran ekplorasiterbatas dan tidak terbatas, minat siswa terhadap hasil belajar passing bawah bola voli,serta interaksi antara metode pembelajaran eksplorasi dan minat siswa terhadap hasil passingbawah bola voli. Penelitian ini eksperimen, dengan disain factorial 2x2. Populasi penelitian232 siswa kelas VIII SMP N 3 Wanasari Brebes. Sampel 40 siswa dibagi 4 kelompok, setiapkelompok 10 siswa pengambilan sampel dengan purposive sampling. Analisis data digunakanuji anova dua arah taraf signifikansi 95%, dilanjutkan uji Tukey. Hasil penelitian: (1) Perbedaanmetode pembelajaran eksplorasi terbatas dan tidak terbatas Fo 79,433 > Ft 4,113,(2) Perbedaan minat siswa tinggi dan rendah Fo = 30,923 > Ft = 4,113, (3) Interaksi antarametode pembelajaran eksplorasi dan minat siswa terhadap hasil passing bawah bola voli Fo =4,230 > Ft = 4,113. Simpulan: (1) Ada perbedaan pengaruh metode pembelajaran ekplorasiterbatas dan tidak terbatas, metode pembelajaran eksplorasi terbatas lebih baik dibandingkanmetode pembelajaran eksplorasi tidak terbatas. (2) Ada perbedaan pengaruh siswa yang memilikiminat tinggi dan minat rendah, minat siswa yang tinggi lebih baik dibandingkan minatsiswa yang rendah. 3) Ada interaksi antara metode pembelajaran eksplorasi dan minat siswaterhadap hasil passing bawah dalam permainan bola voli. Sarankan bagi guru Penjasorkesuntuk meningkatkan hasil belajar passing bawah bola voli dengan metode pembelajaraneksplorasi terbatas dan perlu meningkatkan minat siswa dalam proses pembelajaran.AbstractThe objectives of this research is to examine : 1) the difference between effects of limited exploration learningmethod and unlimited method toward the outcome of forearm passing in volleyball. 2) the differencesbetween the effect of outcome in stundets with high and low interest towards forearm passing in volleyball. 3) the correlation between exploration learning and students’ interest toward the result of forearmpassing in volley ball. Experiment method was employed with factorial 2x2. The population was VIIIgrade students of SMP N 3 Wanasari Brebes District with total 232 students. 40 students were selectedas the sample that was divided into 4 groups consisted of 10 students each group. Purposive samplingwas selected for the technique. Meanwhile the data were analyzed using anova with SPSS-16 program atsignificant rate of 95%. In order to examine the difference among groups, Tukey test was conducted. Theresults indicated that 1) F value for exploration learning method is 79,433 bigger tan F table= 4,113 (Fo =79,433 > Ft = 4,113). 2) F value for students’ interest is 30,923 bigger tan F table= 4,113 (Fo = 30,923 >Ft = 4,113). 3) F value for correlation between exploration learning method and students’ interest towardforearm passing is 4,230 bigger tan F table = 4,113 (Fo = 4,230 > Ft = 4,113). In conclusion: 1) there isa difference between effects of limited exploration learning method and unlimited method toward the outcomeof forearm passing in volleyball. The result of forearm passing with limited exploration method isbetter than the method using unlimited exploration. 2) there is a difference between students with high andlow interest towards the result of forearm passing in volley ball. The result of students with high interest isbetter than students with low interest. 3) There is a correlation between exploration learning method andstudents’ interest toward the result of forearm passing in volley ball. Teachers are suggested to improve theoutcome of forearm passing in volleyball, select the exploration method, develop the exploration learningmethod and notice the factor of interest in the learning process.